Assessment Of Uranium, Lead, Cadmium And Iron In Maternal And Umbilical Cord Blood Samples In Iraq - Hasan Rhaif Al-Sahlanee, Mayyadah (2019)
The assay of blood samples is a preferred method for monitoring the internal exposure of radiological and toxicological contaminants in human body. The objectives of this study were to evaluate the status of uranium (U) radioactivity and selected heavy metals such as lead (Pb), cadmium (Cd) and iron (Fe) in maternal and umbilical cord blood samples for normal and deformed infants in Iraq, and the influence of these elements to the foetus development and to identify predictors of maternal exposure. Additionally, to assess the interactions between these elements in the maternal and umbilical cord blood samples. A cross-sectional study was conducted in three public hospitals (Al-Yarmouk Teaching Hospital, Al-Basrah Maternity and Children Hospital and Al-Shatra Maternity Hospital).